Contributions to control of an asymmetrical six-phase indcution machine / Che Hang Seng - Che, Hang Seng (2012)
This thesis aims to provide additional contributions to control of multiphase machine, with a focus on asymmetrical six-phase induction machine (machine with two three-phase windings spatially displaced by 30°). Using the VSD approach, the machine’s six phase variables can be transformed into six decoupled variables, namely α-β, x-y and two zero sequence variables. For machine with distributed windings, only the α-β components provide useful electro-mechanical energy conversion, while the other components merely produce losses. The studies presented in this thesis are based on this VSD approach, and are separated into three main parts: x-y current control methods, operation with series-connected converters and post-fault control. The first part of this research work looks into the x-y current control methods of the machine using PI controllers. It was found that the x-y currents can be physically interpreted as the circulating current between the two three-phase windings. Depending on the type of asymmetry, x-y currents can appear as positive sequence component, negative sequence component or a combination of both. Hence, performance of PI controller implemented under different reference frame is compared and discussed. In this part of the study, a dead time compensator implemented using resonant controller for x-y currents is also presented. The second part of this work investigates the operation of the six-phase machine with series-connected machine-side converters. Under this topology, the two three-phase windings are supplied by two separate two-level voltage source converters (VSCs) with their dc-link cascaded in series. The series-topology elevates dc-link voltage which gives a reduction in dc-link current and cable size. However, the additional dc-link voltage balancing control is needed to ensure equal voltage sharing. __________________________________________________________________________________________________________ iv This is accomplished by controlling x-y currents, which is a new concept introduced in this work. The final part of the research work deals with post-fault control of six-phase induction machine for a single open-circuit fault. Post-fault control is based on the full order decoupling transformation, to minimise reconfiguration of the controller. Effect of the single open-circuit fault on the machine is discussed. Here, the leg-to-phase voltage relation is identified as an important issue that needs to be addressed when using PI controllers for post-fault operation. Different modes of post-fault operation are analysed and compared. The study considers both the cases where the six-phase machine is configured with single as well as with two isolated neutrals, such that a unified comparison is achieved. In conclusion, this thesis provides insights on the control of x-y currents in six-phase machine based on PI controllers in different reference frame. Two interesting uses of these currents, i.e. for dead time compensation and dc-link voltage balancing have also been presented. In terms of alternative converter topology, the operation of six-phase machine with series-connected machine-side converter is detailed, addressing the merits and demerits of the topology. Lastly, the operation of six-phase induction machine under different modes of post-fault control is studied and compared. All studies are based on simulation in Matlab/Simulink environment and are further verified on a 1.1 kW prototype asymmetrical six-phase induction machine.